Evaluation of a participatory ergonomics intervention in small commercial construction firms. Issue 6 (20th April 2016) - Dale, Ann Marie; Jaegers, Lisa; Welch, Laura; Gardner, Bethany T.; Buchholz, Bryan; Weaver, Nancy; Evanoff, Bradley A.
Abstract : Background: Work‐related musculoskeletal disorders (WMSD) among construction workers remain high. Participatory ergonomics (PE) interventions that engage workers and employers in reducing work injury risks have shown mixed results. Methods: Eight‐six workers from seven contractors participated in a PE program. A logic model guided the process evaluation and summative evaluation of short‐term and intermediate impacts and long‐term outcomes from surveys and field records. Results: Process measures showed good delivery of training, high worker engagement, and low contractor participation. Workers' knowledge improved and workers reported changes to work practices and tools used; contractor provision of appropriate equipment was low (33%). No changes were seen in symptoms or reported physical effort. Conclusions: The PE program produced many worker‐identified ergonomic solutions, but lacked needed support from contractors. Future interventions should engage higher levels of the construction organizational system to improve contractor involvement for reducing WMSD. Am. J. Ind. Med. 59:465–475, 2016. © 2016 Wiley Periodicals, Inc.